2014
DOI: 10.1186/s12909-014-0247-4
|View full text |Cite
|
Sign up to set email alerts
|

Art-making in a family medicine clerkship: how does it affect medical student empathy?

Abstract: BackgroundTo provide patient-centred holistic care, doctors must possess good interpersonal and empathic skills. Medical schools traditionally adopt a skills-based approach to such training but creative engagement with the arts has also been effective. A novel arts-based approach may help medical students develop empathic understanding of patients and thus contribute to medical students’ transformative process into compassionate doctors. This study aimed to evaluate the impact of an arts-making workshop on med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
54
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 26 publications
1
54
0
5
Order By: Relevance
“…The curriculum also aims to help medical students enhance self-awareness for both self-care and in order to improve patient care, 1 2 Through such training, it is hoped that doctors will achieve a better balance in their emotional, psychological and spiritual aspects. Building on our earlier work exploring the use of art to enhance empathy among medical students, 3 4 we present the findings from an arts-based workshop designed to both understand and help medical students cope with their psychosocial stressors.…”
Section: Introductionmentioning
confidence: 99%
“…The curriculum also aims to help medical students enhance self-awareness for both self-care and in order to improve patient care, 1 2 Through such training, it is hoped that doctors will achieve a better balance in their emotional, psychological and spiritual aspects. Building on our earlier work exploring the use of art to enhance empathy among medical students, 3 4 we present the findings from an arts-based workshop designed to both understand and help medical students cope with their psychosocial stressors.…”
Section: Introductionmentioning
confidence: 99%
“…Yang and Yang 17 found that a 4-hour experience with interpreting paintings did not influence medical students' scores on the JSE-S and called for further experimental investigations. Potash et al 18 compared a group of students who made art with a group of students who experienced a "problem-solving" workshop; empathy declined in both groups, without a statistical difference in outcome.…”
mentioning
confidence: 99%
“…A recent review points to the value of incorporating the arts in medical education, especially for teaching self-awareness, openness to other perspectives, and empathy (Haidet et al, 2016). Another study of 3 rd year University of Hong Kong medical students using the JSE as a pre-post measure found that, while the level of empathy declined in both groups over time, with no statistically significant differences between the intervention and control groups, the qualitative data showed that students in an arts-making condition gained insight into self, patients, pain and suffering, and the role of the physician (Potash et al, 2014).…”
Section: Effects Of Physician Empathy On Patientsmentioning
confidence: 99%